Consent, Informal Organization and Job Rewards: a Mixed Methods Analysis. - Laubach, Marty (Social Forces (University of North Carolina Press), 2005)
This study uses a mixed methods approach to workplace dynamics. Ethnographic observations show that the consent deal underlies an informal stratification that divides the workplace into an “informal periphery,” a “conventional core” and an “administrative clan.” The “consent deal” is defined as an exchange of autonomy, voice and schedule flexibility for intensified commitment, and is modeled as a single factor underlying these elements. When constructed as an additive scale, consent allows informal organization to be included in workplace models. Despite its derivation from subjective and informal processes, informal structure exerts an independent effect on objective job rewards such as wages. Reprinted by permission of the publisher.